An Overeview of the Earthquake Preparation among nurses of Muhammadiyah Pekajangan Pekalongan Hospital - Dian Firmansyah; Hana Nafiah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Nurses contribute to disaster management services at all stages, including the pre-disaster stage, namely in the preparedness phase. In emergency and disaster conditions, hospitals have a vital role in responding to health services. Still, often hospital facilities and health workers are also among the victims, so healthcare services cannot be carried out properly when needed. This study aimed to describe PKU Muhammadiyah Pekajangan Hospital nurses' in earthquake disaster preparedness. A purposive sampling technique was used in this study. There were 122 respondents who participated in this study. This research design is a descriptive study.The results of this study showed that the characteristics of age are between 30 to 34 years (27.9%), female (70.5%), three-year Nursing (83.6%) and the majority of work experience are 1-5 years (30.3%). Nurses had a moderate perception (4.41), where the perception of knowledge is medium (4.39), the perception of skills is moderate (4.27), and the perception of family readiness to face disasters is moderate (4.56). The perception of disaster preparafion among nurses at Muhammadiyah Pekajangan Pekalongan Hospital was moderate.